SUSTAINABLE ECONOMIC DEVELOPMENT: GREEN AND CIRCULAR ECONOMIC DURING THE COVID-19 ECONOMIC RECOVERY IN LOMBOK - Susianti, Nurul (IQTISHADUNA, 2023)
This study aims to measure the success of the vision and mission of the NTB governor Mr. Dr. Zulkiflimansyah, S.E, M.Ec as the current NTB Governor, namely the sub-vision of the mission of the original and sustainable NTB. This vision and mission has been implemented since he took office. It is proposed in this study whether this model is able to become an economic recovery model using zero waste-based economic development sub-theme green and circular economy. The method used is descriptive qualitative sampling technique purpose sampling 4 indicators namely policy makers namely DLHK Prov NTB, UMKM Lombok Island, Academics and the community. The results of this study indicate that the form of success of the NTB governor by building a plastic-based school, the central Lombok area has used GAS made from organic waste, 126 waste banks recorded in various locations and special waste management sites Reuse, Reduce and Recycle at 25 points and the last is the 369 location waste team and several forms of training programs conducted at all points in NTB. Some MSMEs have used waste as the basic material for business, the community at the collection and separation stage has not yet been able to manage it into goods of economic value.